Correlation between gross motor coordination and basic coordination capacities in normal-weight and overweight/obese children aged 9–10 years - Sui, Yuan; Cui, Lin; Jia, Binbin; Ding, Xiangyang; He, Min; Da, Yingen; Shi, Yue; Li, Fei; Li, Pan (PeerJ, 2024)
Background Gross motor coordination (GMC) plays a crucial factor in children’s motor development and daily activities. It encompasses various sub-capacities, such as spatial orientation, rhythm, and motor reaction, collectively referred to as basic coordination capacities (BCC). However, children who are overweight and obese (OW/OB) often display poorer GMC. This study aims to examine the impact of gender and weight status (BMI categories) on children’s GMC and BCC. It also seeks to investigate the impact of BCC and BMI on GMC. Method The study involved 266 participants, 135 in the NW group (boys: n = 75; girls: n = 60) and 131 in the OW/OB group (boys: n = 68; girls: n = 63). An NW status is defined by a BMI z-score between ≥−2SD to ≤1SD, while an OW/OB status corresponds to a BMI z-score > 1SD. Physical activity was assessed using the Physical Activity Questionnaire for Children, developed by the University of Saskatchewan, Canada. We used six field tests to evaluate BCC, including single leg standing test (static balance), YBT (dynamic balance), rhythmic sprint test (rhythm), reaction time test (motor reaction), target standing broad test (kinesthetic differentiation), and numbered medicine ball running test (spatial orientation). GMC was evaluated with Kiphard-Schilling’s Body Coordination Test (KTK). Result The motor quotient (MQ) was primarily affected by weight status (F = 516.599, p < 0.001; gender: F = 6.694, p = 0.01), with no significant interaction effect (F = 0.062, p = 0.803). In BCC, gender had a significant main effect on rhythm capacity (F = 29.611, p < 0.001) and static balance (F = 11.257, p = 0.001) but did not significant influence other sub-capacities (p > 0.05). Weight status impacted dynamic balance (F = 11.164, p = 0.001). The interaction of gender and weight status significantly impacted motor reaction (F = 1.471, p = 0.024) and kinesthetic differentiation (F = 5.454, p = 0.02), but did not affect other sub-capacities (p > 0.05). The physical activity was not significant affected by gender (F = 0.099, p = 0.753), weight status (F = 0.171, p = 0.679) and the interactions of two variables (F = 0.06, p = 0.806). In the regression analysis, except motor reaction (p > 0.05), other BCC sub-capacities influenced GMC to varying extents (β = −0.103–0.189, p < 0.05). Nonetheless, only two types of balance significantly mediated the relationship between BMI and GMC (BMI→MQ: β = −0.543, p < 0.001; BMI→YBT: β = −0.315, p < 0.001; BMI→SLS: β = −0.282, p < 0.001; SLS→MQ: β = 0.189, p < 0.001; YBT→MQ: β = 0.182, p < 0.001). Conclusion Compared to gender, the main effect of weight status on most GMC and BCC’s sub-capacities was more pronounced. OW/OB children exhibited poorer GMC, which is related to their reduced static and dynamic balance due to excess weight. Kinesthetic differentiation, spatial orientation, and rhythm capacity are not significantly associated with BMI, but these sub-capacities positively influence gross motor coordination (GMC), except for hand-eye motor reaction.
Keywords: Children; Weight status; Gross motor coordination; Balance; Rhythm ability; Reaction; Kinesthetic differentiation; Spatial orientation; Basic coordination capacities